The Semblance Divine Derivations of Azande Surnames: A Cultural Appraisal of Christianity (African Multidisciplinary Journal of Research, 2022)
Many biblical scholars have written extensively about the personal Divine name of Yahweh (יהוה ) which in English is in reference to the God of the Hebrews. “The Bible is first and foremost about God and his/her dealing with humanity,” (Aloo, 2019: 22). The way in which this God dealt or continues to deal with humanity varies from one community to another, depending on the context. The different names which are attributed to God vary from one community to another. One may easily conclude that the other community or tribe does not know God and does not respect His Divine name. However, the way God revealed His name or Himself to the Hebrew Patriarchs is different from the way in which the same God has been revealing His name or Himself to the different people, including Africans. Each ethnic group occupies a geographical location and characterized by unique cultural traits and worship of God. In reference to Exodus 20:7 which says that “You shall not take the name of the Lord your God in vain; for the Lord will not hold him guiltless who takes his name in vain.” Based on this verse the Jews cannot call or pronounce the name Yahweh (יהוה ) because God’s name is Holy. However, this is not the case among the Azande people in South Sudan. Traditionally, an Azande person cannot call or mention the name of an elder person. But the question is, why do the Azande people name their children with names which are derived directly from the Divine name of Mbori? In reference to Exodus 20:7, does it mean that they are misusing the Divine name of Mbori? Does it mean there is syncretism between Azande tradition religion vis a vis Christianity and the Bible? This article is written to bridge the social gap between the Azande tradition and that of the Jews concerning the use of the Divine name of God. It also explains the perception of the Azande on God’s name and how His name is being used among them. More so, it provides an insight into the Azande cognition and encounter with God in their daily life, thus, providing an objective perspective of the Azande traditional religious view. Furthermore, the article encourages the Azande people to name children with names which stem from the Divine name of Mbori. Since those names exalt God and they explain the goodness of God to the Azande people and, above all, such names are meaningful and reveal the character or identity of the bearers. The practices of giving bad names to children among the Azande is on rise and this needs to be avoided, since those names may bring bad luck to people bearing such evil names. This article discourages husband and wife from using bad names as weapon(s) to fight each other in their marriage. For Christianity to be rooted in the hearts of the Azande, the concept of God needs to be molded into the social aspect of an Azande person and enables him/her to live harmoniously with his/her fellow members in the community.